Preservation of High-Moisture Sorghum Silage Using Combination of Biological and Chemical Additives in the Tropical Region - Ardiansyah, M.; Fitriani, D.; Noviandi, C. T.; Kurniawati, A.; Paradhipta, D. H. V. (Tropical Animal Science Journal, 2025)
This study aimed to investigate the effect of the biological and chemical additives on fermentation characteristics, aerobic stability, and ruminal digestibility of high-moisture sorghum silage. A mixture of Lactiplantibacillus plantarum FNCC 0020 (LP) and Limosilactobacillus fermentum BN21 (LF) was used as a biological additive and potassium sorbate as a chemical additive. At the milk ripening stage (26.8% of DM), sorghum was harvested, chopped to 3-5 cm length, and ensiled into 20 L silo (5 kg) for 100 days. Subsequently, various additives were added, including a control group without additives (CON), LF + LP with a ratio of 1:1 at 1 x 105 cfu/g fresh weight (INO), potassium sorbate at 1 g/kg fresh weight (PS), and INO + PS (MIX). Each treatment used 5 silos as replication. The results showed that INO silage had the lowest (p